Culture and mental health: a Turkish perspective - Aşkın, Rüstem (The European Research Journal, 2022)
Culture and mental health are intertwined concepts. Culture should be regarded as the set of distinctive, spiritual, material, intellectual, and emotional properties of a society or a social group, encompassing lifestyles, ways of living together, value systems, traditions, and beliefs, in addition to art and literature (UNESCO, 2002). Culture consists of different components, including ethnicity, race, religion, age, sex, family values, and the location of the country. It should also be noted that culture is not a static phenomenon. Defining a culture specific to a certain ethnicity, country or region is often not a realistic approach. Many factors, such as the location of a certain city of a country or a certain region of the said city, as well as the inhabitants’ occupational, economic and family positions, have an impact on lifestyles. Globalization, migration, acculturation, assimilation and transition cultures create significant heterogeneity in the very same society. Mental health can be defined as a state of balance that individuals experience both intra- personally and also with other people within their environment. In modern times, we have come to witness that the world we live in transforms at a speed that is challenging to human nature, rapid changes destroy the usual patterns, social ties evolve into ties established in the virtual world, perception replaces reality, and artificial intelligence-like elements turn into new management tools. The spirit of the new century, while flattering human instincts, compresses authenticity, solidarity and peace into ceremonial sentences.